The family/social support and impact on diabetic foot care practice - Rita Sari; Faridah Hashim; Meram Azzani; Janu Purwono (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: In 2040 it is estimated that there will be more than 642 million people with diabetes in the world and as many as 80% of people with diabetes are in developing countries. And every 6 seconds there is one DM patient who dies. WHO estimates that in 2000 the number of people with DM in Indonesia was 8.4 million and in 2030 it will increase to around 21.3 million. In 2015 Indonesia stood in the seventh position with 10 million sufferers. Indonesia is also the third country with 29 million people with impaired glucose tolerance (20 - 79 years) in 2015. The prevalence of diabetes mellitus in Lampung Province has increased with prevalence (1,2%). Purpose: To determine the family/social support and impact on diabetic foot care practice.Method: Using a descriptive correlational design to determine the relationship between variables. The sample is 107 respondents and the sample is taken using purposive sampling. The instrument used in this study was an original Spanish version translated into Bahasa Indonesia. The Social Support Questionnaire-Short Form (SSQ6S) questionnaire a. Foot care behavior was measured based on the foot nursing activity behavior scale for diabetes (FCBS) which consisted of 17 questions. Data analysis used chi-square(α=0,05).Results: A correlation test showed that there was a relationship between family/social support and impact on diabetic foot care practice. p-value = 0.033 (p<0.05). Conclusion: The higher the family/social support and the positive impact on the practice of diabetic foot care.